Commissioning and performance of the CMS silicon strip tracker with cosmic ray muons - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Adam, W; Arnold, B; Bergauer, H; Bergauer, T; Dragicevic, M; Eichberger, M; Erö, J; Friedl, M; Frühwirth, R; et al. (2010)
During autumn 2008, the Silicon Strip Tracker was operated with the full CMS experiment in a comprehensive test, in the presence of the 3.8 T magnetic field produced by the CMS superconducting solenoid. Cosmic ray muons were detected in the muon chambers and used to trigger the readout of all CMS sub-detectors. About 15 million events with a muon in the tracker were collected. The efficiency of hit and track reconstruction were measured to be higher than 99% and consistent with expectations from Monte Carlo simulation. This article details the commissioning and performance of the Silicon Strip Tracker with cosmic ray muons. © 2010 IOP Publishing Ltd and SISSA.